Analysis of Anxiety Level and Self-Confidence towards Sepak Takraw Game Performance - Abdulah Nurrachman; Syahid Nuryasin; Dhani Agusni (Journal of Physical and Outdoor Education, 2026)
This study has a background problem on how much the level of anxiety and self-confidence of athletes influences game performance. This study aims to determine the level of anxiety and self-confidence of athletes and its influence on sepak takraw game performance. This study uses a quantitative method with a one-shot design design which is carried out with one test by distributing questionnaires to athletes. The population in this study were 30 sepak takraw athletes in Cimahi City using total sampling. The data collection instrument used a questionnaire/questionnaire on anxiety and self-confidence. The following are the results of the research data on the level of anxiety and self-confidence of sepak takraw athletes in Cimahi City. The level of anxiety of sepak takraw athletes in Cimahi City is in the "very low" category, namely 60% (18 people). The remaining 30% (9 people) are in the medium, 6.66% (2 people) are in the high category, while 3.33% (1 person) are in the very high category, and the very low category is 0%. And the level of self-confidence of sepak takraw athletes in Cimahi City is in the "High" category, namely 60% (18 people). The remaining 10% (3 people) are in the very high category, 20% (6 people) in the medium category, 10% (3 people) are in the low category, and the very low category is 0%.